Range of Motion Exercise of Arms Increases the Muscle Strength for Post Stroke Patients - Judi Nurbaeni; I Ketut Sudiana; Harmayetty Harmayetty (Universitas Airlangga, 2010)
Introduction: Someone attached by stroke can’t do their activity fluently because stroke can cause the weakness of motor and sensor function. This condition cause physical defect and give effect in social and economic too, because someone who suffered stroke usually still in productive age. The objective of this study was to examine the effect of arm range of motion in the muscle strength of post stroke patient.Methods: Pre experimental pre–post test design was used in this study. Population of this study was post stroke patient in Wijayakusuma ward dr. Soedono Hospital and total samples were 11 respondents. Independent variable was arm range of motion exercise, dependent variable was strength of arm muscle. Data were collected by observation with manual muscle testing of Lovelt, Naniel and Worthinghom and then analyzed using wilcoxon signed rank test with signi fi cant level of α ≤ 0.05.Result: The result showed that 11 respondents had increased their strength of muscle (p = 0.04).Conclusion: It can be concluded that the strength of muscle increased after get arm range of motion exercise. When range of motion had been done Ca+ will be activated by cell so that happen integrity of muscle protein. If Ca+ and troponin had been activated, actin and myosin would have been defensed, so that can moved the skeletal and followed by muscle contraction, expand, outgrow and had a tonus. This condition can showed the strength of muscle.